FinFET modeling for IC simulation and design : using the BSIM-CMG standard /: using the BSIM-CMG standard. (2015) - Chauhan, Yogesh; Lu, Darsen Duane; Sriramkumar, Vanugopalan; Khandelwal, Sourabh; Duarte, Juan Pablo; Payvadosi, Navid; Niknejad, Ai; Hu, Chenming
No abstract available